Enhancing die corner accuracy using path modification strategy in wire electrical discharge machining of Monel 400. (January 2018) - Selvakumar, G; Thiruppathi Kuttalingam, KG; Selvaraj, M; Manohar, J
In this study, path modification strategy is used to improve the accuracy of the die corner produced in wire electrical discharge machining process. Based on Taguchi's L18 array, experiments are performed on Monel 400 alloy. The influence of the machine-controllable factors such as wire tension, open-circuit voltage, pulse-on time, pulse-off time and additional travel and uncontrollable factors namely corner angles and flushing nozzle height on the performance measures such as surface roughness, cutting speed, and corner error are studied. The outcome of this study reveals that the path modification value in terms of additional travel of 0.5 mm improves the corner accuracy of the profile by 35% as compared to the profile machined without adopting path modification strategy. The analyses of scanning electron micrographs are carried out. Finally, an optimal technological guideline is reported for ready industrial use.